Comparative Evaluation of Chemical Composition, Phenolic Compounds, and Antioxidant and Antimicrobial Activities of Tropical Black Bolete Mushroom Using Different Preservation Methods - Kumla, Jaturong; Suwannarach, Nakarin; Tanruean, Keerati; Lumyong, Saisamorn (Foods, 2021)
Tropical black bolete, Phlebopus portentosus, provides various nutritional benefits and natural antioxidants to humans. In this study, the chemical composition, phenolic compounds, and antioxidant and antimicrobial activities of fresh mushroom samples and samples stored for a period of one year using different preservation methods (drying, brining, and frozen) were investigated. The results indicated that the brining method significantly reduced the protein and fat contents of the mushrooms. The polyphenol and flavonoid contents of the frozen sample were not significantly different from that of the fresh sample. The results revealed that an inhibition value of 50% (IC50) for the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay of the extract of the dried and frozen samples was not statistically different from that of the fresh sample. The IC50 value of 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid (ABTS) assay and ferric reducing antioxidant power (FRAP) value in the extract of the frozen sample were not found to be significantly different from those of the fresh sample. Furthermore, the lowest degree of antioxidant activity was found in the extract of the brined sample. Additionally, the antimicrobial activities of the extracts of the fresh and frozen samples were not significantly different and both extracts could have inhibited the growth of all tested Gram-positive bacteria and Pseudomonas aeruginosa.